Industrial compliant robot bases in interaction tasks: a force tracking algorithm with coupled dynamics compensation. Issue 8 (7th July 2016) - Roveda, Loris; Pedrocchi, Nicola; Vicentini, Federico; Molinari Tosatti, Lorenzo
SUMMARY: Light-weight manipulators are used in industrial tasks mounted on mobile platforms to improve flexibility. However, such mountings introduce compliance affecting the tasks. This work deals with such scenarios by designing a controller that also takes into account compliant environments. The controller allows the tracking of a target force using the estimation of the environment stiffness (EKF) and the estimation of the base position (KF), compensating the robot base deformation. The closed-loop stability has been analyzed. Observers and the control law have been validated in experiments. An assembly task is considered with a standard industrial non-actuated mobile platform. Control laws with and without base compensation are compared.